Key Word Use in Letters of Recommendation for Ophthalmology Residency Applicants According to Race, Gender, and Achievements - Aggarwal, Sahil; Grob, Seanna; Banerjee, Dhruba; Putzel, Preston J.; Tao, Jeremiah (Journal of Academic Ophthalmology, 2018)
Objectives To identify differences in letters of recommendation (LORs) of applicants to a single ophthalmology residency program by gender, race, academic performance, and match outcome.Design This was a retrospective analysis of LORS for 2,523 applicants (7,569 letters) to the University of California, Irvine ophthalmology residency program from 2011 to 2018.Methods Programming scripts were employed to determine the number of times 22 key words from four thematic categories (standout words, ability, grindstone, and compassion) appeared in LORs for each applicant. A chi-square test was performed to assess for possible differences in the presence of each key word by the following characteristics: gender, underrepresented minority (URM) status, Alpha Omega Alpha (AOA) membership, the United States Medical Licensing Exam (USMLE) Step 1 score, and match outcome. Linear regressions were created to determine the frequency at which words in each thematic category appeared according to the same baseline characteristics.Results In the LORs, females were more likely to be described as “empathetic” (p = 0.002), URMs were more likely to be described as “caring” (p = 0.002), high Step 1 scorers (≥240) were more likely to be described as “outstanding” (p = 0.002), and matched students were more likely to be described as “exceptional” (p = 0.001), “outstanding” (p < 0.001), and “superb” (p = 0.001). Standout words appeared more often in the LORs of AOA members, matched candidates, and high Step 1 scorers (p < 0.001 for all comparisons). “Competent” appeared more commonly in LORs for low Step 1 scorers (p < 0.001) and unmatched applicants (p = 0.001).Conclusion This study identifies differences in LORs by gender, URM status, and achievement including successful ophthalmology residency match. Females and URMs were more likely to be described as “empathetic” and “caring,” respectively; otherwise, we detected no gender or racial disparities in key word use in LORs. Candidates with high USMLE Step 1 scores or AOA membership had a higher frequency of standout words in their LORs. Whether they were truly more qualified in various dimensions or if they benefited from a halo effect bias warrants further investigation. There was a significant difference in the number of standout words in LORs between matched and unmatched applicants, suggesting that key word frequency may be a relevant metric for LOR appraisal.
Keywords: letters of recommendation; ophthalmology; bias; gender; underrepresented minority; Alpha Omega Alpha